DR4-Associated Death Receptor Signal Promotes Cartilage Damage in Patients With Kashin-Beck Disease. (December 2021) - Wu, Shixun; Yi, Zhi; Ling, Ming; Liu, Shizhang; Sun, Zhengming; Guo, Xiong
Purpose . To explore the relationship between the death receptor (DR) and the pathological progression of Kashin-Beck disease (KBD). Design . KBD cartilage samples were collected from 15 patients diagnosed according to the "National Diagnostic Criteria of KBD" in China. In vitro monolayer chondrocytes were cultured in complete medium. Caspase-3 and caspase-8 activities in chondrocytes were analyzed using a kit. Nuclear morphology was observed by Hoechst 33258 staining, apoptosis was verified by flow cytometry analysis, and DR molecules were detected using Western blotting and quantitative real-time reverse transcription polymerase chain reaction analysis. Results . Early apoptotic rates of KBD and osteoarthritis (OA) chondrocytes were higher than those of normal control (NC) cells. Excessive apoptotic nuclei were observed in OA and KBD cells after Hoechst 33258 staining. Activities of both caspase-3 and caspase-8 were higher in KBD and OA cells than in NC cells. The average DR4 mRNA level in KBD cells was 3.301-fold higher than that in NC cells, Fas-associating protein with death domain (FADD) transcript level in KBD cells was 2.528-fold higher than that in NC cells. Western blot analyses showed that FAS, DR4, DR5, caspase-3, and FADD were upregulated in the KBD and OA groups compared with the NC group. High expression of caspase-8 in KBD compared with NC was verified, whereas cellular FLICE-inhibitory protein (c-FLIP) in KBD was significantly downregulated. Conclusions . KBD and OA chondrocytes showed obvious FADD-caspase-dependent apoptosis, which is related to the DR pathway. Apoptosis in KBD articular cartilage is mainly related to FAS/DR4-FADD-caspase signaling, and OA is associated with FAS/DR4/DR5-FADD-caspase signaling.